PENGARUH KANDUNGAN ABU DAN ZAT TERBANG TERHADAP MAKSIMUM FLUIDITAS BATUBARA FORMASI TANJUNG DI DAERAH SEKAKO, KALIMANTAN TENGAH: THE INFLUENCE OF ASH AND VOLATILE MATTER CONTENTS ON MAXIMUM FLUIDITY OF TANJUNG FORMATION COAL IN SEKAKO AREA, CENTRAL KALIMANTAN PROVINCE - Wiranata, Beny; Amijaya, Hendra; Anggara, Ferian; Tanggara, Deddy N.S.P. (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2020)
High to low volatile bituminous coals of Tanjung Formation in Central Kalimantan Province is known to be potentially used as a metallurgical or coking coal. Coal maximum fluidity is one important parameter which is strongly connected to the quality of the coke produced. This study aims to determine the relationship between coal maximum fluidity and its volatile matter and ash content. Four coal from A seam and 6 coal from B seam of Tanjung Formation in Sekako area were sampled using a ply by ply channel sampling method. Samples are dominated by bright coal and banded bright coals lithotype. All coal samples are subjected to proximate and Gieseler plastometer analysis in the laboratory. The coal samples Laboratory results show that coal in the study area have ash content ranging from 2,79 to 9,05 (wt%, adb), volatile matter contents varies from 35,14 to 39,50 (wt%, adb) and coals maximum fluidity varies from 22263 to 49029 (ddpm). Further data evaluation indicates that in the study area, coal ash content are negatively correlated (r= -0.656, R2= 0.431) and had no significant effect on the maximum of coal fluidity (r = -0,656, R2 = -0,431 and sig. 0,055 > 0,05). On the other hand, coal volatile matter are positively correlated (r = 0.794; R2 = 0.6301) and had a significant effect (sig. 0.003 <0.05) on the maximum fluidity of coal. The increase of ash content causes the decrease of coal maximum fluidity, whereas the increase of coal volatile matter causes the increase of coal maximum fluidity. The correlation of volatile matter content and coal maximum fluidity can be expressed by an equation of y = 6327,9x - 200248.